Egg consumption risk due to different metal residues: An estimation from two chicken egg types (exotic and local) collected from Sokoto, Nigeria - Umar, AI; Sarkingobir, Yusuf; Abubakar Shagari, Kasimu; Abu Abdulkarim, Yalli (Environmental and Toxicology Management, 2023)
Eggs are important component of human diet worldwide. They provide the human body with diverse array of substances including metal elements. Due to pollution the eggs can incorporate metals at levels that are harmful. Thus, the objective of this work was to determine the levels of Ca, Mg, Fe, Zn, Cd, Pb, and Cr in eggs in Sokoto, Nigeria and health risk therewith. The metals were determined using atomic absorption spectroscopy. The results reveal, significantly (p<0.05) different concentrations of metals in commercial/ exotic and local chicken eggs in Sokoto, Nigeria as follows: The zinc (Local: 35.0 ± 1.5 ppm, Exotic: 30.12 ± 2.6 ppm) metal is the most elevated metal, followed by magnesium (Local:15.0 ± 0.05 ppm, Exotic:10.02 ± 1.5 ppm), then iron (Local: 7.0 ± 0.001 ppm, Exotic: 4.02 ± 0.001 ppm), then calcium (Local: 6.21 ± 0.01 ppm, Exotic: 5.01 ± 0.005 ppm). Others lower levels of metals are recorded by chromium (Local: 3.01 ± 0.05 ppm, Exotic: 4.51 ± 0.05 ppm), cadmium (0.061 ± 0.001 ppm detected in Exotic), and lead (Local: 0.05 ± 0.002 ppm, Exotic: 0.20 ± 0.002 ppm). The levels of essential metals found in eggs in this study are low, and levels of Cr, Cd, and Pb in exotic eggs are elevated. Similarly, health risk assessment result shows a public health concern. Care needs to be taken when consuming eggs by the public.